Disputes Over the Number of Votes in the Simangambat Village Head Election from the Perspective of Siyasah Qadhaiyah - Audy Zahra, Amalia Putri; Khalid (State of Islamic Institute Langsa, 2024)
The village head election in Simangambat has sparked a dispute over the number of votes that has attracted the attention of the community, authorities and legal experts. The conflict reflects the challenges of local democracy, which is often characterized by dissatisfaction and conflict. This research explores the complexity of the dispute through the perspective of Siyasah Qadhaiyah, an Islamic legal framework that emphasizes justice, benefit and peaceful conflict resolution. Using a descriptive-analytical qualitative approach, data was collected through in-depth interviews, direct observation, and analysis of official documents, taking into account the local social and cultural context. The results show that the application of Siyasah Qadhaiyah principles can provide a fair and effective solution in resolving disputes in Simangambat. The principle of deliberation allows all parties to express their views openly and reach a mutually acceptable agreement, reduce tension, and prevent conflict escalation, creating an atmosphere conducive to peaceful resolution. The findings of this research not only enrich the legal literature on village head elections, but also offer a model of harmonious and sustainable dispute resolution. This model can be adopted by other villages facing similar situations, increasing public trust in the election process and village governance. This research opens new avenues for the application of Siyasah Qadhaiyah in local governance, potentially making a significant contribution to the development of legal systems and democracy at the village level in Indonesia.